Expression of microRNAs targeting heat shock protein B8 during in vitro expansion of dental pulp stem cells in regulating osteogenic differentiation. (November 2019) - Yao, Shaomian; Li, Chunhong; Budenski, Angelle M.; Li, Patricia; Ramos, Alexandra; Guo, Steven
Highlights: Rat dental pulp stem cells (DPSCs) reduce osteogenic ability after expansion. Upregulation of miR-215 and miR-219a-1-3p expression after expansion of DPSCs. miR-215 and miR-219a-1-3p can downregulate heat shock protein B8 expression. miR-215 and miR-219a-1-3p are involved in maintaining osteogenic ability of DPSCs. Inhibiting miR-215 and miR-219a-1-3p partly recovers the lost osteogenic ability. Abstract: Objective: The objectives of this study were (a) to determine the differentially expressed microRNAs that can target heat shock protein B8 (HspB8) during in vitro expansion of dental pulp stem cells (DPSCs); (b) to identify microRNAs involved in posttranscriptional regulation of HspB8 expression; and (c) to determine if HspB8-targeting microRNAs play roles on osteogenic differentiation of DPSCs. Design: DPSCs were established from rat first molars and expanded in vitro until the passage that cells lost osteogenic potential. TargetScan was used to predict the microRNAs that target HspB8 mRNA. Stem-loop quantitative RT-PCR was conducted to identify the HspB8-targeting microRNAs that were upregulated in late passages. The microRNAs mimics were transfected into DPSCs to assess their effects on HspB8 expression and on osteogenic differentiation. Results: let-7b-5p, miR-98-5p, miR-215, miR-219a-1-3p and miR-295-5p were found to consistently increase expression in DPSCs after expansion. HspB8 mRNA and/or protein were significantly decreased in the DPSCs after transfection of miR-215 and miR-219a-1-3p mimics; whereas no significant reduction was seen after transfecting let-7b-5p, miR-98-5p and miR-295-5p mimics. When subjecting the transfected DPSCs to osteogenic induction, reduction of calcium deposition or osteogenic marker expression were observed with miR-215, miR-219a-1-3p and miR-295-5p transfection. Conclusions: Increased expression of miR-215 and miR-219a-1-3p downregulates HspB8 expression, which contributes to the reduction of osteogenic capability of DPSCs. Increased expression of miR295-5p also causes a reduction of osteogenic differentiation, but not involved in HspB8.